Corporate Criminal Sanction in Omnibus Law for Forest Destruction in Indonesia: Review of Law Number 11 of 2020 on Job Creation - Rohmy, Atikah Mardhiya; Setiyono, H; Supriyadi, Supriyadi (Al-Risalah, 2021)
The Green Economy has turned into a growing trend in the fourth industrial revolution (industry 4.0), particularly after the Covid-19 pandemic hit the world. The efforts to increase the investment (investor domination) in Law Number 11 of 2020 on Job Creation are apparently not reinforced by other instruments and overlook the principle of sustainable development. This study aims to analyze the legislative policy regarding the criminal sanction of the corporation which commits criminal acts related to prevention and eradication of forest destruction after the enactment of Law No. 11 of 2020 on Job Creation. The main observed issue is in the incompatible formulation of administrative sanctions and criminal sanctions. Hence, to analyze such matters, this qualitative research employs a normative legal perspective. This study finds the incompatible formulation of 'Criminal Sanctions' on Corporations, as it is stated in Article 82 Paragraph (3), Article 84 Paragraph (3), Article 85 Paragraph (2), and Article 96 Paragraph (2). Moreover, there is also an unfitting interpretation of 'Administrative Sanctions' in the "forms of administraÂtive fines".